Primary Pulmonary Hypertension - Abdul Rani, Mohammed Fauzi (Malaysian Medical Association, 2000)
Primary pulmonary hypertension(PPH) is a rare disease. The annual incidence in the West is 1-2 cases per million population per year. A recent WHO symposium in 1998 has produced a consensus on classification, methods of screening, risk assessment and treatment. PPH is a diagnosis of exclusion after all other secondary causes of pulmonary hypertension are ruled out. Current treatment strategy involves acute vasodilator drug trial where positive responders are treated with high dose calcium channel blockers and anticoagulation. Those who do not show positive response may be commenced on intravenous prostacyclin. Surgical treatment is one option for patients with severe PPH or for symptomatic relief. Prognosis in general is very poor.